2016
DOI: 10.1371/journal.pone.0149693
|View full text |Cite
|
Sign up to set email alerts
|

The Mare Model to Study the Effects of Ovarian Dynamics on Preantral Follicle Features

Abstract: Ovarian tissue collected by biopsy procedures allows the performance of many studies with clinical applications in the field of female fertility preservation. The aim of the present study was to investigate the influence of reproductive phase (anestrous vs. diestrous) and ovarian structures (antral follicles and corpus luteum) on the quality, class distribution, number, and density of preantral follicles, and stromal cell density. Ovarian fragments were harvested by biopsy pick-up procedures from mares and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 48 publications
2
27
1
1
Order By: Relevance
“…Perhaps some paracrine factors may be involved, besides aspects related to possible differences in the blood distribution in the ovarian parenchyma, like suggested by Alves et al. (). Our study did not cover such aspects, but it is known that hormones, growth factors and gases can impact follicular degeneration (Araujo et al., ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Perhaps some paracrine factors may be involved, besides aspects related to possible differences in the blood distribution in the ovarian parenchyma, like suggested by Alves et al. (). Our study did not cover such aspects, but it is known that hormones, growth factors and gases can impact follicular degeneration (Araujo et al., ).…”
Section: Discussionmentioning
confidence: 85%
“…More recently, a new hypothesis was presented to elucidate the uneven distribution of follicles in the equine species. According to Alves et al (2016), there is a variation in follicle quality, class distribution and follicle and stroma cell densities. These recent publications portray the growing interest of the scientific community in the mapping of the equine follicles.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, no differences between the follicular diameters of CL-bearing and non-CL-bearing ovaries were obtained. During diestrus, in the presence of CL, multiple structures, such as small, medium antral and preovulatory follicles, can be present in the ovary of the mare [30]. Due to the great heterogenicity of follicle sizes that can occur even in mares for which the phase of the estrous cycle is unknown [31], one can presume not to expect significant differences between follicle sizes in CL-bearing and non-CL-bearing groups.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the in vitro development of follicles in ovarian fragments could be influenced by the origin of the samples. We formed this hypothesis based on the recent data from Alves et al (2016), who showed changes in follicular activity and distribution according to the phase of the mare's oestrous cycle. In this way, we can hypothesize that the previous stage of ovarian activity may interfere with the in vitro follicular growth, including the response to FSH, which might explain the different results for the in vitro culture of the follicles in mares and other species with reproductive seasonality.…”
Section: Discussionmentioning
confidence: 99%